Rancang Bangun Mitigasi Gerakan Tanah Berbasis Data Vertical Electrical Sounding: Studi Kasus Kelurahan Tawang Sari, Kota Semarang - Michael Adrian Indrajati (Jurnal Ilmiah Geologi PANGEA, 2026)
Investigating soil instability is crucial in mitigating geotechnical risks to infrastructure, particularly in rapidly developing regions such as Semarang City. Tawangsari Village, situated within an alluvial plain, exhibits potential soil instability due to its lithological composition and anthropogenic influences. This study aims to assess the soil instability potential and identify appropriate mitigation strategies to reduce the risk of ground movement. The research employs the Schlumberger geoelectric configuration using the Vertical Electrical Sounding (VES) method. Measurements were conducted at three locations, each reaching a depth of approximately 30 meters. Analysis results reveal a low-resistivity soil layer at depths ranging from 14.03 to 23.08 meters, indicating a high susceptibility to instability. This layer is predominantly composed of clay, whose physical properties are inadequate to support structural loads, thereby increasing the likelihood of soil movement. Based on geoelectric interpretation, the recommended mitigation approach includes soil stabilization via grouting and the installation of anchors within the clay-sand layer to enhance its bearing capacity. Additionally, pile installation along the nearby riverbank is advised to minimize slope failure risks associated with ground movement. These mitigation strategies are favored due to their cost-effectiveness and feasibility, allowing implementation without necessitating the dismantling of existing structures.